Gezi Resistance in the Absence of Participation - Okten, Ayse Nur; Kurtarir, Erhan; Cekic, Tuba Inal (KARE PUBL, 2013)
Construction sector was an engine of last ten year's economic development and this sector has nurtured by rapid urban regeneration processes. In this period, Turkeys last quarter's popular concepts; localization, governance and participation had put on the shelf totally. Therefore, in the last 5 years, urban policy and planning became the most important issues of the central government. Construction facilities put on the agenda directly by central government. Naturally, as Turkey's biggest metropolitan area Istanbul has been the focus of construction agenda. Projects and plans leading spatial development also leads and gives direction to fundamental rights and life styles. Decision-making processes of such urban plans and projects also reflect the way of using participation rights. Experiences from Istanbul, particularly Gezi resistance, give an opportunity for critical evaluation of the participation problematic in our planning process. Civil resistance and disobedience that has been arising from and urban movement has revealed that how the space has been politicized day by day. Urban planning has gone out of controlling mechanism of the planning system and became an intervention tool of the authority for daily life. As an abandoned concept, participation in planning constitutes the main theme of this article.
Keywords: Gezi resistance; participation; participatory planning; Public Administration